Nanospectroscopy of Infrared Phonon Resonance Enables Local Quantification of Electronic Properties in Doped SrTiO3 Ceramics. (5th September 2018) - Lewin, Martin; Baeumer, Christoph; Gunkel, Felix; Schwedt, Alexander; Gaussmann, Fabian; Wueppen, Jochen; Meuffels, Paul; Jungbluth, Bernd; Mayer, Joachim; Dittmann, Regina; Waser, Rainer; Taubner, Thomas
Abstract: Among the novel materials for electronic applications and novel device concepts beyond classical Si‐based CMOS technology, SrTiO3 represents a prototype role model for functional oxide materials: It enables resistive switching, but can also form a 2D electron gas at its interface and thus enables tunable transistors. However, the interplay between charge carriers and defects in SrTiO3 is still under debate. Infrared spectroscopy offers the possibility to characterize structural and electronic properties of SrTiO3 in operando, but is hampered by the diffraction‐limited resolution. To overcome this limitation and obtain nanoscale IR spectra of donor‐doped Sr1‐x Lax TiO3 ceramics, scattering‐type scanning near‐field optical microscopy is applied. By exploiting plasmon–phonon coupling, the local electronic properties of doped SrTiO3 are quantified from a detailed spectroscopic analysis in the spectral range of the near‐field 'phonon resonance'. Single crystal‐like mobility, an increase in charge carrier density N and an increase in ε∞ at grain boundaries ( µ ≈ 5.7 cm 2 V −1 s −1, N = 7.1 × 10 19 cm −3, and ε∞ = 7.7) and local defects ( µ ≈ 5.4 cm 2 V −1 s −1, N = 1.3 × 10 20 cm −3, and ε∞ = 8.8) are found. In future, subsurface quantification of defects and free charge carriers at interfaces and filaments in SrTiO3 can be envisioned. Abstract : Infrared near‐field optical microscopy is used to non‐destructively quantify the electronic properties of doped SrTiO3 on the nm scale. This is enabled by exploiting plasmon–phonon coupling and a detailed analysis of the near‐field optical phonon resonance. Thus, the accumulation of electrons at grain boundaries in donor‐doped ceramics is revealed and as a proof of principle resistively switched spots are identified.